2009
DOI: 10.1007/s11606-009-0970-4
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Experience of Scholarly Activities is Associated with Higher Satisfaction with Residency Training

Abstract: The majority of residents surveyed thought that research activity was worthwhile. Residents' participation in research activity was associated with higher levels of satisfaction with residency training. Implementing measures to overcome existing barriers may have educational benefits for residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 16 publications
1
57
1
8
Order By: Relevance
“…Participation in scholarly projects enhances an individual’s self-satisfaction, self-esteem and satisfaction with residency training [19]. There are tangible personal benefits stemming from becoming the expert in a field, presenting the results of one’s own project, participation in national professional meetings and seeing one’s name in print.…”
Section: Discussionmentioning
confidence: 99%
“…Participation in scholarly projects enhances an individual’s self-satisfaction, self-esteem and satisfaction with residency training [19]. There are tangible personal benefits stemming from becoming the expert in a field, presenting the results of one’s own project, participation in national professional meetings and seeing one’s name in print.…”
Section: Discussionmentioning
confidence: 99%
“…In 1994, the RRC-IM established a new requirement that ''prior to the completion of training, each resident must demonstrate acceptable scholarly activity,'' defined as ''original research, comprehensive case reports or review of clinical and research topics (Levine, Hebert, & Wright, 2005). Takahashi O et al in 2009 concluded that majority of residents thought that research activity was worthwhile and that participation in research activity was associated with higher levels of satisfaction with residency training (Takahashi et al, 2009). Till 2011, approximately 67% of the resident research grants funded work has been published in high impact factor journals.…”
Section: Number Of Grants Awardedmentioning
confidence: 99%
“…Furthermore, it has also been shown that optimal performance in daily clinical practice requires a wide range of skills, and accordingly, doctors with scientific training during their medical education usually express better abilities regarding making decisions through using information collected from different sources. Several studies have targeted the relationship between the engagement of research activities by medical students and medical education and it has been found that there was a positive impact on the motivation of medical students 8,9 .…”
Section: Introductionmentioning
confidence: 99%